Estimación del nivel de potasio en sangre mediante las pendientes del QRS del electrocardiograma en pacientes renales crónicos - Bukhari, Syed Hassaan Ahmed; Sánchez, Carlos (Jornada de Jóvenes Investigadores del I3A, 2021)
Noninvasive estimation of serum potassium concentration can help prevent ventricular arrhythmias and sudden cardiac death in patients with chronic renal failure (CKD), but current outpatient estimation methods are limited. In this study, we estimated serum potassium concentration by evaluating the slopes of the “QRS complex” of the electrocardiogram in 29 patients with CRF during and after hemodialysis.